Genome-wide analysis of radish AHL gene family and functional verification of RsAHL14 in tomato - Chen, Weifang; Chen, Leifu; Cui, Lei; Liu, Zhixiong; Yuan, Weiling (Frontiers in Plant Science, 2024)
The AT-hook motif nuclear localized (AHL) gene family is a highly conserved transcription factors involved in plant growth, development, and stress responses. However, AHLs have not been systematically analyzed in radish (Raphanus sativus). Therefore, we performed genome-wide identification and expression pattern, gene structure, and function verifications of radish AHLs. We identified 52 radish AHLs (RsAHL1-RsAHL52), which were unevenly distributed across nine chromosomes. Phylogenetic analysis showed that the RsAHLs were divided into two clades (A and B) and subdivided into three types (I, II, and III). Collinearity analysis revealed that the 52 RsAHLs produced 49 repeat events. Tissue expression profiles revealed differential expression of RsAHLs across different tissues, with higher expression observed in flower organs, particularly petals and anthers. qRT-PCR results indicated that RsAHLs responded to abscisic acid, methyl jasmonate, and abiotic stress (low and high temperatures and drought). Additionally, RsAHL14 induced a dwarf phenotype in tomato plants, and RsAHL14-overexpression tomato plants presented significantly decreased expression levels of the gibberellin (GA) synthetic genes ent-Copalyl diphosphatase, GA3ox-3/-4/-5, and GA20ox-1/-2/-3, but significantly increased expression of the degradation gene GA2ox-1/-3. Thus, RsAHL14 might affect plant growth by regulating GA content. Collectively, our study comprehensively identified RsAHLs in radish and provided a reference for further research on these genes.